Genetic analysis suggests functional interactions between the N- and C-terminal domains of the TetA(C) efflux pump encoded by pBR322. - McNicholas, P (1995)
Genetic analysis of the tetA(C) gene of pBR322 indicates the importance of two-cytoplasmic loops in the TetA(C) protein (P. McNicholas, I. Chopra, and D. M. Rothstein, J. Bacteriol. 174:7926-7933, 1992). In this study, we characterized second-site suppressor mutations that suggest a functional interaction between these two cytoplasmic regions of the protein.